Relationships between neuropsychological impairments and functional outcome eight years after severe traumatic brain injury: Results from the PariS-TBI study. (29th July 2021) - Vallat-Azouvi, Claire; Swaenepoël, Marie; Ruet, Alexis; Bayen, Eleonore; Ghout, Idir; Nelson, Gaelle; Pradat-Diehl, Pascale; Meaude, Layide; Aegerter, Philippe; Charanton, James; Jourdan, Claire; Azouvi, Philippe
ABSTRACT: Background/objectives: The objective was to assess the relationships between neuropsychological impairments, functional outcome and life satisfaction in a longitudinal study of patients after a severe traumatic brain injury (TBI) (PariS-TBI study). Patients: Out of 243 survivors, 86 were evaluated 8 years post-injury. They did not significantly differ from patients lost-to-follow up except for the latter being more frequently students or unemployed before the injury. Methods: Outcome measures included the Glasgow Outcome Scale-Extended (GOS-E), a functional independence questionnaire, employment, mood, fatigue and satisfaction with life. Neuropsychological outcome was assessed by two ways: performance-based outcome measures, using neuropsychological tests and patient and relative-based measures. Results: Neuropsychological measures were not significantly related to initial injury severity nor to gender, but were significantly related to age and education. After statistical correction for multiple comparisons, cognitive testing and cognitive questionnaires were significantly correlated with most outcome measures. By contrast, satisfaction with life was only related with patient-rated questionnaires. A regression analysis showed that the Trail-Making-Test-A was the best predictor of functional outcome, in addition to education duration. Conclusions: Cognitive measures, particularly slowed information processing speed, were significant indicators of functional outcome at a long-term post-injury, beyond and above demographics or injury severity measures.